2018
DOI: 10.3389/fneur.2018.00289
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Endovascular Treatment of Early Recurrent Proximal Middle Cerebral Artery Occlusion: Case Report and Brief Review of the Literature

Abstract: Mechanical thrombectomy (MT) is the gold standard treatment for large vessel occlusion (LVO) stroke of the anterior circulation. Whether MT can also be effectively and safely performed in early recurrent LVO is largely unclear. We present the case of a middle-aged patient who was successfully treated by MT for right proximal middle cerebral artery (MCA) occlusion with excellent outcome. One day after discharge (9 days after the first MT), the patient was readmitted with wake-up stroke. MRI again revealed right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…To our knowledge there are reports of repeated MT in patients with AIS [3,6]. However, no patients with AIS complicated with uremia undergoing repeated MT treatments in a short time were reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge there are reports of repeated MT in patients with AIS [3,6]. However, no patients with AIS complicated with uremia undergoing repeated MT treatments in a short time were reported.…”
Section: Discussionmentioning
confidence: 97%
“…Fortunately, endovascular mechanical thrombectomy (MT) can significantly improve the prognosis of patients with LVO stroke [1,2]. In addition, for LVO recurring in the short term, it is possible to perform repeated MTs [3]. However, patients with end-stage renal disease undergoing maintenance dialysis have a higher incidence of both ischemic and hemorrhagic stroke than the general population [4,5], there have been no reports of repeated MT for LVO patients with dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…13 Those investigators report that, although repeated thrombectomy may exacerbate damage to the vascular endothelium, which increases the risk of complications such as vasospasm, arterial dissection and ICH, repeated MT therapy for early recurrence of LVO seems feasible in carefully selected patients. 13 Those investigators report that, although repeated thrombectomy may exacerbate damage to the vascular endothelium, which increases the risk of complications such as vasospasm, arterial dissection and ICH, repeated MT therapy for early recurrence of LVO seems feasible in carefully selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fandler et al reported a patient who underwent MT and achieved good outcome after two LVOs in 9 days. 13 Those investigators report that, although repeated thrombectomy may exacerbate damage to the vascular endothelium, which increases the risk of complications such as vasospasm, arterial dissection and ICH, repeated MT therapy for early recurrence of LVO seems feasible in carefully selected patients. However, the patient in that report did not have renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wealth of data that has been obtained from the major trials and numerous case series, there remain unanswered questions including the safety and necessity of repeat thrombectomy. Previous studies have shown that repeat thrombolytic therapy is safe [18][19][20][21][22], however, there is limited data on the safety of recurrent mechanical thrombectomy [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%